Estratégias de inovação e mudança organizacional: o Programa de Racionalização e competitividade da Caixa Econômica Federal - Silva, Antonio Claudio Lima da (2004)
The aim of this dissertation is to identify - by means of the study case of the implementation of PRC - Programa de Racionalização e Competitividade in Caixa Econômica Federal - if there are patterns of organizational responses and solutions that can indicate a basic model of a typical brazilian organizational change and innovation. Since brazilian turbulent business environment has developed enterprises highly adaptable to the environment provocations by de adoption of many organizational change management models, this study, on one hand, reviews the bibliography about the theme. On the other hand , describes the context and the sort of management model experienced by CAIXA, between 1989 and 1998, in order to register and systemize information that will allow to survey, along the time, common characteristics that can describe this typical brazilian innovation and organizational change model. The results of field research supported by bibliographic examination allow to conclude that the change process experienced by the organization by the time of the implementation of the program has been aroused by a sort of variables either from the internaI context or the externaI context. Furthermore, it was possible to conclude that it was easier for the organization to manage the strategic, structural and human perspectives and it was more difficult to manage the technological, cultural and political perspectives. The study, therefore, confirms that some perspectives of the change process presented practices of organizational innovation and that some others perspectives could not be reproduced in a trustable way, expressive scale and reasonable costs.